Microbial Community and Fermentation Characteristics of Native Grass Prepared Without or With Isolated Lactic Acid Bacteria on the Mongolian Plateau - You, Sihan; Du, Shuai; Ge, Gentu; Wan, Tao; Jia, Yushan (Frontiers in Microbiology, 2021)
This study aimed to isolate and identify lactic acid bacteria (LAB) from the native grass and naturally fermented silage from the Mongolian Plateau. The effect of selected strains on bacterial community and quality of native grass silage was also studied. Strains XM2, 265, and 842 could grow normally at 15°C–30°C, pH 4.0–8.0, and NaCl 3 and 6.5%; they were identified as Lactiplantibacillus plantarum subsp. plantarum, Pediococcus acidilactici, and Latilactobacillus graminis, by sequencing 16S rRNA, respectively. The three strains (XM2, 265, and 842) and one commercial additive (L) were used as inoculants and singularly added to the native grass. Compared to the control, the dry matter content was significantly (p < 0.05) lower in L and XM2 groups. The water-soluble carbohydrate content was significantly (p < 0.05) higher in control than in other groups. Compared with the control, the crude protein and ammonia nitrogen contents were significantly (p < 0.05) higher and lower in the LAB-treated groups, and the acid and detergent fiber contents were significantly (p < 0.05) reduced in the L and XM2 groups than those in other groups. There was a significant (p < 0.05) difference in the pH value, lactic acid content, and lactic acid-to-acetic acid ratio in L and XM2 groups than in other groups. Compared with the control, the number of LAB was significantly (p < 0.05) higher in LAB-treated silages, whereas no significant (p > 0.05) differences were observed in yeast and aerobic bacteria in all groups. Compared to the control, the Shannon index was significantly (p < 0.05) reduced. Simpson and Chao1 were significantly (p < 0.05) increased. Principal coordinate analysis based on the unweighted UniFrac distance showed clear separation of the bacterial community in fresh materials and LAB-treated silages. Besides, compared to the control, the principal coordinate analysis of LAB-treated silages was also separate. After 30 days of fermentation, the relative abundance of Firmicutes increased and was the primary phylum in all silages. Compared with the control, the abundance of Firmicutes and Proteobacteriawas significantly (p < 0.05) higher and lower in L and XM2 groups. In contrast, no significant differences were observed among control, 265, and 842 groups. At the genus level, the relative abundance of Lactobacillus, Enterobacter, Pediococcus, and Weissella was increased and dominated the native grass fermentation. Compared with the control, the abundance of Lactobacillus was significantly (p < 0.05) higher in L, XM2, and 842 groups, while no significant (p > 0.05) differences were observed between the control and 265 groups. The abundance of Pediococcus was higher than that in other groups. Consequently, the results demonstrated that LAB significantly influenced silage fermentation by reconstructing microbiota, and Lactobacillus was the dominant genus in the native grass silages. Furthermore, the results showed that strain XM2 could effectively improve the silage quality, and it is considered a potential starter for the native grass silage.